2021
DOI: 10.1017/s1460396921000595
|View full text |Cite
|
Sign up to set email alerts
|

Comparative dosimetry of brachytherapy treatment planning between a volume-based plan by CT and a point-based plan by TAUS in CT datasets for brachytherapy

Abstract: Aim: To evaluate comparative dosimetry of brachytherapy treatment planning between a volume-based plan by computed tomography (CT) and a point-based plan by transabdominal ultrasound (TAUS) in CT datasets for brachytherapy. Materials and methods: From 2019 to 2021, 59 different datasets of CT images were collected from 38 patients treated by intracavitary brachytherapy with tandem ovoid or tandem ring applicators. At that time, TAUS was performed to prevent uterine perforation and to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Pintakham [94] performed a study to evaluate the dosimetry comparison of brachytherapy delineation using two distinct methods: a volume-based plan utilising computed tomography (CT) and a point-based plan employing transabdominal ultrasound (TAUS) in CT datasets for brachytherapy. The results showed that the point-based plan performed by TAUS had better outcomes for both the intended targets and the organs at risk, in comparison to the volume-based plan carried out by CT. TAUS's point-based technique led to a close closeness between D98 and HR-CTV.…”
Section: Discussionmentioning
confidence: 99%
“…Pintakham [94] performed a study to evaluate the dosimetry comparison of brachytherapy delineation using two distinct methods: a volume-based plan utilising computed tomography (CT) and a point-based plan employing transabdominal ultrasound (TAUS) in CT datasets for brachytherapy. The results showed that the point-based plan performed by TAUS had better outcomes for both the intended targets and the organs at risk, in comparison to the volume-based plan carried out by CT. TAUS's point-based technique led to a close closeness between D98 and HR-CTV.…”
Section: Discussionmentioning
confidence: 99%
“…Pintakham [60] conducted a research to assess the dosimetry comparison of brachytherapy treatment planning using two different methods: a volume-based plan using computed tomography (CT) and a point-based plan utilising transabdominal ultrasonography (TAUS) in CT datasets for brachytherapy. The findings indicated that the point-based plan implemented by TAUS demonstrated superior values for both targets and organs at risk compared to the volume-based plan executed by CT. TAUS's point-based strategy resulted in a proximity of D98 to HR-CTV.…”
Section: Discussionmentioning
confidence: 99%